Tax Footnotes Readability and CEO Narcissism: Evidence from Indonesia - Arfian Erma Zudana; Kiddy Novian; Rakha Pangestu Setiawan; Sherlin Sherlin (Business Economic, Communication, and Social Sciences (BECOSS) Journal, 2022)
CEO Narcissism has the potency to influence individual characteristics positively or negatively. We aim to examine the relationship between narcissism as CEO-level characteristics and tax footnotes readability. We measure narcissism using the CEOs’ photos on the firms’ annual reports. Using 799 firm-year Indonesia listed firms from 2015 through 2019, we find that higher CEO narcissism is related to a higher tax footnote readability. This result is robust for alternative measures of readability. By examining the relationship between CEO narcissism and tax footnotes readability, we provide an additional important factor to boards for consideration during the CEO selection. We also offer insight for shareholders or investors to consider CEO traits, namely narcissism, in assessing and interpreting tax footnotes readability.